Durvalumab therapy following chemoradiation compared with a historical cohort treated with chemoradiation alone in patients with stage III non–small cell lung cancer: A real-world multicentre study. (January 2021) - Desilets, Antoine; Blanc-Durand, Félix; Lau, Sally; Hakozaki, Taiki; Kitadai, Rui; Malo, Julie; Belkaid, Wiam; Richard, Corentin; Messaoudene, Meriem; Cvetkovic, Lena; Kazandjian, Suzanne; Tehfe, Mustapha; et al.
Abstract: Background: The PACIFIC trial demonstrated that durvalumab therapy following chemoradiation (CRT) was associated with improved overall survival (OS) in patients with stage III non–small cell lung cancer (NSCLC). It is unclear whether the results obtained as part of randomised controlled trials are a reflection of real-world (RW) data. Several questions remain unanswered with regard to RW durvalumab use, such as optimal time to durvalumab initiation, incidence of pneumonitis and response in PD-L1 subgroups. Methods: In this multicentre retrospective analysis, 147 patients with stage III NSCLC treated with CRT followed by durvalumab were compared with a historical cohort of 121 patients treated with CRT alone. Survival curves were estimated using the Kaplan-Meier method and compared with the log-rank test in univariate analysis. Multivariate analysis was performed to evaluate the effect of standard prognostic factors for durvalumab use. Results: Median OS was not reached in the durvalumab group, compared with 26.9 months in the historical group (hazard ratio [HR]: 0.56, 95% confidence interval [CI]: 0.37–0.85, p = 0.001). In the durvalumab group, our data suggest improved 12-month OS in patients with PD-L1 expression ≥50% (100% vs 86%, HR: 0.25, 95% CI: 0.11–0.58, p = 0.007). There was no difference in OS between patients with a PD-L1 expression of 1–49% and patients with PD-L1 expression <1%. Delay in durvalumab initiation beyond 42 days did not impact OS. Incidence of pneumonitis was similar in the durvalumab and historical groups. In the durvalumab group, patients who experienced any-grade pneumonitis had a lower 12-month OS than patients without pneumonitis (85% vs 95%, respectively; HR: 3.3, 95% CI: 1.2–9.0, p = 0.006). Conclusions: This multicentre analysis suggests that PD-L1 expression ≥50% was associated with favourable OS in patients with stage III NSCLC treated with durvalumab after CRT, whereas the presence of pneumonitis represented a negative prognostic factor. Highlights: We present the largest real-world study of durvalumab use after chemoradiation in stage III non–small cell lung cancer. PD-L1 expression ≥50% was associated with longer progression-free survival (PFS) and overall survival (OS). No differences in OS were observed in patients with delays in durvalumab initiation. The presence of any-grade pneumonitis was associated with worse OS.